Delay Minimization for BAC-NOMA Offloading in UAV Networks - Haodong Li; Zhengkai Yin; Changsheng Chen (Sensors)
The rapid deployment and enhanced communication capabilities of unmanned aerial vehicles (UAVs) have enabled numerous real-time sensing applications. These scenarios often necessitate task offloading and execution under stringent transmission delay constraints, particularly for time-critical applications such as disaster rescue and environmental monitoring. This paper investigates the improvement of MEC-based task offloading services in energy-constrained UAV networks using backscatter communication (BackCom) with non-orthogonal multiple access (BAC-NOMA). The proposed BAC-NOMA protocol allows uplink UAVs to utilize downlink signals for backscattering tasks instead of transmitting through uplink NOMA. A resource allocation problem is formulated, aimed at minimizing offloading delays for uplink users. By converting the initially non-convex problem into a convex one, an iterative algorithm is developed to solve it. Simulation results demonstrate that the proposed protocol significantly reduces offloading delays relative to existing benchmarks.